2024
DOI: 10.1186/s12961-023-01093-4
|View full text |Cite|
|
Sign up to set email alerts
|

The response of the Military Health System (MHS) to the COVID-19 pandemic: a summary of findings from MHS reviews

Alysa Pomer,
Satish Munigala,
Christian L. Coles
et al.

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic caused major disruptions to the US Military Health System (MHS). In this study, we evaluated the MHS response to the pandemic to understand the impact of the pandemic response in a large, national, integrated healthcare system providing care for ~ 9 million beneficiaries. Methods We performed a narrative literature review of 16 internal Department of Defense (DoD) reports, including revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], it was reported that Tracey Perez Koehlmoos was erroneously listed as being affiliated with affiliation 2 in addition to affiliation 3. The correct affiliations are given in this Correction and the original article has been updated.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that Tracey Perez Koehlmoos was erroneously listed as being affiliated with affiliation 2 in addition to affiliation 3. The correct affiliations are given in this Correction and the original article has been updated.…”
mentioning
confidence: 99%